The Application of 2nd Generation Intact Stability Criteria to Ship Operating in Indonesia Waterway: Pureloss Stability. Issue 1 (January 2021) - Anggara, S; Maskar, R D; Hariadi, M R F; Ichsan, L M; Zaky, M; Kurniawan, A
Abstract: The development of 2 nd Generation intact stability criteria has entered final chapter since nearly one-decade intensive work. The instrument is intended to measure ship stability in dynamic aspect on wave which has not been considered by its predecessor, IS Code 2008. Prior to enforcement, BKI has taken early preparation to establish inhouse calculation tool independently for assessing ship stability in accordance with the first 2 level of vulnerability criteria, i.e. Pureloss Stability . Semi performance based and direct assessment are introduced as the concept behind the calculation, thus the procedure is quite complex and need more time to proceed which leads to utilize automation. Furthermore, a set number of types of ship with various dimension have been tested to the system in respect to Indonesia environmental condition. The results show that typical ships are vulnerable to certain criteria which may beneficial for operator to gain initial precaution.